Z opisu wyrażeń modalnych w Kodeksie prawa kanonicznego - Łapa, Romana (Poznańskie Spotkania Językoznawcze, 2015)
The text is about modality from a linguistic point of view. The author takes a broad understanding of a modal category (modality indentified with communicative intention) and analyses the so called basic modal units: verbs and predicates, which together with an infinitive create a verbal construction. She examines a function of the mentioned expressions in the Code of Canon Law. Willing to accept a specific character of contexts with modal expressions, she includes in the description conclusions coming from earlier study of newspaper texts, homilies and speeches of John Paul II.